Family functioning, coping strategy, and suicidal ideation among adolescents - Chin, Wen Cong; Wu, Shin Ling *; Fitriana, Mimi (Routledge, 2020)
Background and aim: Adolescent suicide has become a central issue around the world, including in Malaysia, which needs attention. The current study investigated the mediating effect of coping strategy in the association between family functioning and suicidal ideation among adolescents in Kuala Lumpur, Malaysia. Method: A total of 852 school-attending adolescents aged 13–17 years were recruited by multistage cluster sampling. The relationships between all the study variables were analysed using Pearson’s correlation. Moreover, the mediation model was tested using SPSS PROCESS macro, while sex differences in suicidal ideation were examined using independent samples t-test. Results: Results showed that family cohesion, family flexibility, and problem-focused coping negatively correlated with adolescents’ suicidal ideation. Problem-focused coping also mediated the association between family flexibility and suicidal ideation. There was a significant difference in suicidal ideation for males and females. Conclusion: Family functioning and coping strategy are related to adolescents’ suicidal ideation, while problem-focused coping plays a crucial role in the relationship between family flexibility and suicidal ideation.